The Effect of Good Corporate Governance on The Value of IDX 30 Companies Listed on The Indonesia Stock Exchange - Nida Awvada; Vitriyan Espa; Muhammad Fahmi; Syarif M Helmi; Nina Febriana Dosinta (Poltanesa, 2025)
This study aims to examine the influence of Good Corporate Governance (GCG) on firm value in companies listed in the IDX30 index on the Indonesia Stock Exchange. The background of this research stems from the growing importance of GCG implementation, particularly after the 1997 Asian financial crisis, where internal issues such as weak institutional supervision and poor investment decisions were identified. The study adopts a quantitative approach, utilizing secondary data from annual reports and financial statements of IDX30 companies. Analytical methods include classical assumption tests and multiple regression analysis to determine the effect of GCG variables such as board of commissioners, independent commissioners, audit committee, and institutional ownership on firm value. The results show that GCG practices significantly affect firm value. This finding reinforces the notion that good governance practices enhance transparency, accountability, and stakeholder trust, which are critical in boosting the company's market performance and attractiveness to investors.